2004
DOI: 10.1103/physreva.69.023809
|View full text |Cite
|
Sign up to set email alerts
|

Optical bistability in semiconductor microcavities

Abstract: We report the observation of polaritonic bistability in semiconductor microcavities in the strong coupling regime. The origin of bistability is the polariton-polariton interaction, which gives rise to a Kerr-like nonlinearity. The experimental results are in good agreement with a simple model taking transverse effects into account.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
375
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(392 citation statements)
references
References 20 publications
9
375
3
5
Order By: Relevance
“…Photon antibunching and squeezing were theoretically predicted and experimentally demonstrated in pioneering resonance fluorescence experiments [4][5][6][7] . In strong contrast, despite several theoretical proposals 8,9 , the continuous variables regime has seen so far only very few experimental achievements [10][11][12] of squeezed states of light in semiconductor materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photon antibunching and squeezing were theoretically predicted and experimentally demonstrated in pioneering resonance fluorescence experiments [4][5][6][7] . In strong contrast, despite several theoretical proposals 8,9 , the continuous variables regime has seen so far only very few experimental achievements [10][11][12] of squeezed states of light in semiconductor materials.…”
mentioning
confidence: 99%
“…Especially interesting is the case of degenerate polariton four-wave mixing in which the strong nonlinearities originating in the polaritonpolariton interactions allow describing the polariton system as an effective Kerr medium whose refractive index depends on the light intensity 12,27,28 . Kerr media are well known to be very efficient sources of quadrature-squeezed light.…”
mentioning
confidence: 99%
“…The effect of electromagnetically induced transparency (EIT) has led to many interesting nonlinear optical phenomena. Two interesting nonlinear optical phenomenon, which has been studied in the recent years in the atomic media are Kerr nonlinearity [10,11,12,13]and optical bistability [14,15,16,17]. It is shown that a large Kerr nonlinearity with reduced probe absorption causes the nonlinear optics to be studied at low light power [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] The theory of this effect was developed within the framework of different mean-field models based either on equations for the polariton occupation number, 9 where the fractions of excitons and cavity photons are connected through the Hopfield coefficients, 14 or on coupled equations for excitons and photons. 15 The bistability of coherent spin ensembles described in the two-mode approximation by the spinor Gross-Pitaevskii equation with an external pump has been reported too.…”
Section: Introductionmentioning
confidence: 99%